Challenges and opportunities in RSV vaccine development: Meeting report from FDA/NIH workshop. Issue 41 (22nd September 2016) - Roberts, Jeffrey N.; Graham, Barney S.; Karron, Ruth A.; Munoz, Flor M.; Falsey, Ann R.; Anderson, Larry J.; Marshall, V.; Kim, Sonnie; Beeler, Judy A.
Abstract: Respiratory syncytial virus (RSV) is the most common cause of serious acute lower respiratory illness in infants and young children and a significant cause of disease burden in the elderly and immunocompromised. There are no licensed RSV vaccines to address this significant public health need. While advances in vaccine technologies have led to a recent resurgence in RSV vaccine development, the immune correlates of protection against RSV and the immunology of vaccine-associated enhanced respiratory disease (ERD) remain poorly understood. FDA's Center for Biologics Evaluation and Research (CBER) and NIH's National Institute of Allergy and Infectious Diseases (NIAID) organized and co-sponsored an RSV Vaccines Workshop in Bethesda, Maryland on June 1 and 2, 2015. The goal of the conference was to convene scientists, regulators, and industry stakeholders to discuss approaches to RSV vaccine development within the context of three target populations - infants and children, pregnant women, and individuals >60 years of age. The agenda included topics related to RSV vaccine development in general, as well as considerations specific to each target population, such as clinical and serological endpoints. The meeting focused on vaccine development for high income countries (HIC), because issues relevant to vaccine development for low and middle income countries (LMIC) have been discussed in other forums. This manuscript summarizes the discussion of clinical, scientific, and regulatory perspectives, research gaps, and lessons learned.